2021
DOI: 10.1186/s13100-021-00251-1
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of transposable elements (TEs) during the murine submandibular gland development

Abstract: The submandibular gland (SG) is a relatively simple organ formed by three cell types: acinar, myoepithelial, and an intricate network of duct-forming epithelial cells, that together fulfills several physiological functions from assisting food digestion to acting as an immune barrier against pathogens. Successful SG organogenesis is the product of highly controlled and orchestrated genetic and transcriptional programs. Mounting evidence links Transposable Elements (TEs), originally thought to be selfish genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…This was also a concern in our previous bulk RNA-Seq study, where the RNA selection protocol was based on polyA selection. In turn, we demonstrated that under these conditions, approximately ~70% of all TEs could be retrieved (15). Interestingly, another reports have revealed a similar finding, in that such polyA-selection protocol might hinder detection of other repetitive elements, such as satellites, but not of TEs (35,36).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…This was also a concern in our previous bulk RNA-Seq study, where the RNA selection protocol was based on polyA selection. In turn, we demonstrated that under these conditions, approximately ~70% of all TEs could be retrieved (15). Interestingly, another reports have revealed a similar finding, in that such polyA-selection protocol might hinder detection of other repetitive elements, such as satellites, but not of TEs (35,36).…”
Section: Discussionsupporting
confidence: 84%
“…We have previously analyzed TE expression in the murine SMG using bulk RNA-Seq. Briefly, we found that more than 9000 TEs became differentially regulated across the E14.5, E16.5, E18.5, P1, P28 and P70 timepoints (15). Moreover, through statistical association analysis, we predicted genes that could be potentially modulated by TEs.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Although most TEs are now genetically fixed, they can still become transcriptionally active, which can impact gene regulation 25 . Current evidence supports their role as regulatory elements in health and disease [26][27][28] . In particular, there are many examples of their global derepression and subsequent activation in a wide array of cancer types (reviewed in 29 ).…”
Section: Introductionmentioning
confidence: 93%